The supreme gods of the Bosporan Kingdom : Celestial Aphrodite and the Most High God - Ustinova, Yulia. (Religions in the Graeco-Roman World, 1999)
This is the first systematic study of the cults of the Bosporan Kingdom, which existed in South Russia in the first centuries AD. The research is based on a variety of sources: archaeological evidence and inscriptions, largely unknown to the non-Russian readers, as well as historical and literary texts. The religion of the Bosporus is viewed in this monograph as a blend of Greek and indigenous Iranian traditions. Its first part is dedicated to the cult of Celestial Aphrodite. The second part examines the controversial cult of the Most High God and its alledged Jewish affinities. The book, illustrated with thirty figures, is an important contribution to the understanding of the religious life in Greek colonies, and the history of Eastern Mediterranean in Late Antiquity.